Reconstructing Past Elevations From Triple Oxygen Isotopes of Lacustrine Chert: Application to the Eocene Nevadaplano, Elko Basin, Nevada, United States - Ibarra, Daniel E.; Kukla, Tyler; Methner, Katharina A.; Mulch, Andreas; Chamberlain, C. Page (Frontiers in Earth Science, 2021)
Triple oxygen isotope measurements are an emerging tool in paleoclimate reconstructions. In this contribution we develop the application of triple oxygen isotope measurements to lacustrine sediments to reconstruct past elevations. We focus on a well-constrained sample set from the Eocene North American Cordillera (Cherty Limestone Formation, Elko Basin, NV, USA, 42-43.5 Ma) on the east side of the elevated Nevadaplano. We present triple oxygen isotope measurements on freshwater lacustrine chert samples from the Cherty Limestone Formation. Across an evaporation trend spanning 6.5‰ in δ18O values we observe a negative correlation with ’17O ranging from –0.066‰ to –0.111‰ (RL = 0.528), with an empirical slope (chert, δ’17O vs. δ’18O) of 0.5236. Additionally, we present new carbonate clumped isotope (Δ47) temperature results on the overlying fluvial-lacustrine Elko Formation, which indicate an error-weighted mean temperature of 32.5 ± 3.8 ºC (1σ), and evaporatively enriched lake water spanning δ18O values of –3.7 to +3.5 ‰ (VSMOW). Paired chert and carbonate δ18O values demonstrate that co-equilbrium among the carbonate and chert phases is unlikely. Thus, as also previously suggested, it is most likely that Elko Basin chert formed during early diagenesis in equilbirium with pore waters that reflect evaporatively 18O-enriched lake water. Using this scenario we apply a model for back-calculating unevaporated water composition to derive a source water of δ’18O = –16.1 ‰ (VSMOW), similar to modern local meteoric waters but lower than previous work on paired δ18O- δD measurements from the same chert samples. Further, this back-calculated unevaporated source water is higher than those derived using δD measurements of Late Eocene hydrated volcanic glass from the Elko Basin (average δ’18O equivalent of approximately –18.4 ‰, VSMOW). This suggests, assuming Eocene meteoric water ’17O values similar to today (~0.032 ‰), either that: 1) the hypsometric mean elevation recorded by the lacustrine Cherty Limestone was lower than that derived from the average of the volcanic glass δD measurements alone; or 2) there was hydrogen exchange in volcanic glass with later low δD meteoric fluids. Nonetheless, our new findings support a relatively high (~2.5 to 3 km) plateau recorded in the Elko Basin during the mid-Eocene.